1992
DOI: 10.1007/bf00183227
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary consequences of nonrandom damage and repair of chromatin domains

Abstract: Some evolutionary consequences of different rates and trends in DNA damage and repair are explained. Different types of DNA damaging agents cause nonrandom lesions along the DNA. The type of DNA sequence motifs to be preferentially attacked depends upon the chemical or physical nature of the assaulting agent and the DNA base composition. Higher-order chromatin structure, the nonrandom nucleosome positioning along the DNA, the absence of nucleosomes from the promoter regions of active genes, curved DNA, the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 302 publications
0
59
0
Order By: Relevance
“…An alternative explanation is variation in the efficiency of DNA repair (Filipski 1987(Filipski , 1988Eyre-Walker 1994). Various types of DNA repair are known to vary in their efficiency over the scale of a gene (Bohr et al 1987;Boulikas 1992) and this could generate variation in the pattern of mutation (Eyre-Walker 1994). Selection could also be responsible for the variation in base composition within genes.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation is variation in the efficiency of DNA repair (Filipski 1987(Filipski , 1988Eyre-Walker 1994). Various types of DNA repair are known to vary in their efficiency over the scale of a gene (Bohr et al 1987;Boulikas 1992) and this could generate variation in the pattern of mutation (Eyre-Walker 1994). Selection could also be responsible for the variation in base composition within genes.…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to the conditions that surround DNA, such as mutagenic agents and the DNA repairing system. Different local chromatin structures can induce an attack of different types of DNA damaging agents [24]. The condensation and decondensation of chromatin structures, which is accompanied by inactivation and activation of a gene, are related to the sensitivity to a nuclease involved in the repairing system [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that mutational patterns vary across mammalian chromosomes and different chromosomal regions evolve at different rates (e.g. Filipski 1988;Wolfe et al 1989;Boulikas 1992;Eyre-Walker 1992;Holmquist and Filipski 1994;Matassi et al 1999). Variations in mutation rates across chromosomes correlate with replication timing and could be related to the different efficiency of DNA repair mechanisms.…”
Section: Chargaff Rules [A] ‫ס‬ [T] and [G] ‫ס‬ [C]mentioning
confidence: 99%